Common mental disorders and associated factors among high school students in Debre Markos Town, Northwest Ethiopia: an institutional-based cross-sectional study. Issue 11 (4th November 2022) - Melkam, Mamaru; Nenko, Goshu; Demilew, Demeke
Abstract : Background: Common mental disorders include anxiety, depression and somatic symptoms. These pose significant public health problems because of their serious effects on personal well-being, social and occupational functions. They also can affect the health and quality of life of people in adolescence, because this age group has been vulnerable to different factors. According to the American Psychiatry Association, more than 60% of adolescents fulfil the criteria for at least one common mental disorder. Despite the high burden of the disorders, there are limited studies in Ethiopia; therefore, this study provided the prevalence of common mental disorders among students in Ethiopia. Methods: From 5 May to 30 May 2021, an institutional-based cross-sectional study was undertaken. Simple random sampling was used to select study participants from each class level across all high schools. A self-administered survey was used that included Self-Reporting Questionnaire 20, Oslo Social Support Scale-3 and other semistructured instruments for the screening of common mental disorders. Data were checked, coded and entered into Epi-Data V.4.6.0, then exported to SPSS V.20 for analysis. Bivariable and multivariable logistic regression analyses were done to identify factors associated with common mental disorders. Adjusted ORs with 95% CIs were calculated and variables with a p value of <0.05 were considered as significantly associated with common mental disorders. Results: A total of 600 high school students were recruited with a response rate of 93.2%. The overall prevalence of common mental disorders among the participants was 181 (32.4%). Being female (adjusted OR (AOR)=1.93; 95% CI: 1.27 to 2.99), a family history of mental illness (AOR=2.23; 95% CI: 1.15 to 4.35), poor social support (AOR=3.14; 95% CI: 1.51 to 6.54), a history of non-physical sexual abuse (AOR=2.09; 95% CI: 1.21 to 3.62) and a history of physical sexual abuse (AOR=2.43; 95% CI: 1.29 to 4.59) were significantly associated with common mental disorders. Conclusion and recommendation: The prevalence of common mental disorders was 32.4% among students; therefore, it is recommended facilitating institutional-based intervention services in the school to decrease the contributing factors for the common mental disorders.